Comparing intrinsic and extrinsic motivation in bilingual children and their monolingual peers - Greenwald, Declan G.; Shan, Liantao; Boldt, Tori A.; Truong, Brandon B.; Gonzalez, Guido S.; Chen, Carolyn H.; Corpus, Jennifer Henderlong (Frontiers in Education, 2023)
Building from previous research showing a bilingual advantage in school, the present study investigated the link between bilingualism and academic motivation. We asked whether bilingual students would exhibit higher levels of intrinsic or extrinsic motivation than their monolingual peers, how intrinsic and extrinsic motivation would change over time, and the extent to which those forms of motivation would be in tension with one another. Relative to their monolingual peers, we expected bilingual students to (1) report higher levels of both intrinsic and extrinsic forms of motivation, and (2) show a weaker negative correlation between intrinsic and extrinsic forms of motivation. Bilingual status, intrinsic motivation, and extrinsic motivation were measured at two time points in a diverse sample of 1047 3rd-grade through 8th-grade students (851 monolingual, 196 bilingual). Bilingual students reported significantly higher levels of both intrinsic and extrinsic motivation than monolingual students. They also showed a sharper decline in intrinsic motivation from fall to spring. Intrinsic and extrinsic forms of motivation were negatively correlated for monolinguals, but unrelated for bilinguals, suggesting that the two motive types may be less antagonistic among students who speak a language other than English at home. These differences may be driven by both cognitive (e.g., executive functioning skills) and cultural (e.g.., family cohesion, interdependent orientation) factors, and may inform educators who wish to support learning for students from diverse groups.